Theory of the Principles: Strengths and Weaknesses - De Fazio, Federico (2019)
This work aims to reconstruct the state of the art in the field of the theory of principles, understanding by this an analytical theory oriented to explain the logical structure of this kind of norms. We aim to corroborate two hypotheses. The first one states that the classificatory difference’s thesis between principles and rules has not been refuted by any argument or counterexample so far. The second one claims that, notwithstanding the foregoing, the question about how the concept and structure of principles should be represented remains unanswered.